Penerepan Problem Based Learning untuk Meningkatkan Sikap Ilmiah dan Hasil Belajar Kognitif Mahasiswa Biologi FKIP Universitas Muhammadiyah Riau - Purwanto, Hadi; Ramadhani, Witri; Azim, Fauzan (Journal of Education and Teaching, 2024)
Scientific attitude and the cognitive learning ecology of plant biology students’ FKIP  Islamic University of Riau has not been satisfactory. The experiment was conducted in the second semester of the academic year 2014/2015 in the fourth grade D in Biology FKIP  Islamic University of  Riau. This study was conducted in two cycles, each cycle consisting of four stages.Data were collected through observation sheets filled in by the observer and data achievement test given the end of the cycle. Observation sheet used to determine the scientific attitude and cognitive learning outcomes of students during the learning takes place. The results of  data analysis Cycle 1 and Cycle 2 shows the increase in the scientific attitude and cognitive learning out comes of students’. Scientific attitude of students’ increased from 60.97% to 73.00% with an increase of 12.03%. Cognitive learning outcomes of students in Cycles1 and Cycles 2 also increase. The number of students’ who pass increased from 54. 54% to 81. 81% . In general it can be concluded that the use of models of Problem Based Learning can enhance scientific attitude and cognitive learning outcomes of students’ in biology semester IV D FKIP Islamic University of Riau.